(untitled) (International Journal of Engineering and Computer Science, 2013)
Performance Management began around 60 years ago as a source of income justification and was used to determine an employee’s wage based on performance. Organizations used Performance Management to drive behaviors from the employees to get specific outcomes. In practice this worked well for certain employees who were solely driven by financial rewards. However, where employees were driven by learning and development of their skills, it failed miserably. The gap between justification of pay and the development of skills and knowledge became a huge problem in the use of Performance Management. We are developing a system that maintains various positions like employee, supervisor and review manager for each department and competencies of each position, for the organization. These positions and competencies are classified and only are accessible or maintained by the Human Resource Department. Employees are supposed to fill a self-assessment on the competencies required for his or her position. Upon completion the form is sent to the review manager and his score for each employee with some comments is also taken. And the final score of the employee is calculated by taking the average of 3. Reports are generated in various levels likedepartment, position, and competency.